Hasil Belajar Pembelajaran Model Student Facilitator And Explaining Dengan Penggunaan Media Audio Visual - Burhan Noerdin (Lembaga Pengembangan Kinerja Dosen, 2021)
. Based on the results of observations, learning subjects Basic Knowledge of Mechanical Engineering in Vocational High Schools showed low learning outcomes. The purpose of this study is to improve student learning outcomes by using audio-visual media in the student facilitator and explaining learning model. This research is a class action research consisting of two cycles, each cycle consisting of planning, action, observation, and reflection activities. The research subjects were 35 male students in class X Machining at SMK Negeri 1 Cibeber for the 2020/2021 academic year. Based on the results of the written test conducted at the end of cycle I, an average value of 69.92 was obtained with 72% classical completeness. Implementation of improvements in cycle II increased student learning outcomes, with an average score of 78.30 and 76.92% classical completeness.